2016
DOI: 10.1038/npp.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-Induced Synaptic Alterations in Thalamus to Nucleus Accumbens Projection

Abstract: Exposure to cocaine induces addiction-associated behaviors partially through remodeling neurocircuits in the nucleus accumbens (NAc). The paraventricular nucleus of thalamus (PVT), which projects to the NAc monosynaptically, is activated by cocaine exposure and has been implicated in several cocaine-induced emotional and motivational states. Here we show that disrupting synaptic transmission of select PVT neurons with tetanus toxin activated via retrograde trans-synaptic transport of cre from NAc efferents dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 62 publications
4
85
0
Order By: Relevance
“…When Hamlin and colleagues (Hamlin et al 2009) demonstrated a role for the PVT in context-induced reinstatement, they also showed that this renewal of drug-seeking behavior engaged the PVT-NAc shell pathway, which included the entire rostrocaudal extent of the PVT. Additionally, the PVT-NAc pathway is involved in the acquisition of cocaine self-administration (Neumann et al 2016), as well as mediating symptoms during drug withdrawal (Zhu et al 2016). Recently, however, it was shown that pharmacological inactivation of the anterior, but not the posterior, PVT increases sucrose-seeking behavior upon reward omission, and that this behavior is specifically mediated by aPVT projections to the NAc shell (Do-Monte et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When Hamlin and colleagues (Hamlin et al 2009) demonstrated a role for the PVT in context-induced reinstatement, they also showed that this renewal of drug-seeking behavior engaged the PVT-NAc shell pathway, which included the entire rostrocaudal extent of the PVT. Additionally, the PVT-NAc pathway is involved in the acquisition of cocaine self-administration (Neumann et al 2016), as well as mediating symptoms during drug withdrawal (Zhu et al 2016). Recently, however, it was shown that pharmacological inactivation of the anterior, but not the posterior, PVT increases sucrose-seeking behavior upon reward omission, and that this behavior is specifically mediated by aPVT projections to the NAc shell (Do-Monte et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, however, we targeted a specific nucleus that had been identified as a key player in these Pavlovian learning processes (Flagel et al 2011a, Haight and Flagel 2014, Haight et al 2015, Yager et al 2015, Haight et al 2017), to determine whether the same nucleus acts to encode the incentive value of a cue that was previously paired with operant drug delivery. While it is known that the neural circuitry mediating Pavlovian conditioning can differ from that mediating instrumental behavior (Ostlund et al 2007, Yin et al 2008, Wassum et al 2011), the paraventricular nucleus of the thalamus appears to be involved in both (Hamlin et al 2009, James et al 2010, Browning et al 2014, Haight et al 2015, Matzeu et al 2015, Neumann et al 2016, Do-Monte et al 2017, Matzeu et al 2017, Otis et al 2017). The current findings support a role for this nucleus in the attribution of incentive value to reward cues and suggest that, in a subset of individuals, the PVT acts to suppress the learned incentive value of such cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been long understood that the plasticity potential of a network is in part determined by the fraction of synapses which exist in a silent state, and the proportion of silent synapses is regulated both throughout development (4-5) and in response to diseases or drugs (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Despite a growing appreciation of the overall importance of silent synapses in mature neural networks, a systematic analysis of quantification methods for this parameter, to our knowledge, is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…distribution falls below zero, which are biologically irrelevant estimates. Since negative values are expected, yet have not been reported from FRA (8)(9)(10)(11)(16)(17)(18)(19)(20)(21), it is possible that these negative values returned from the equation are systematically set to a biologically relevant value of 0% silent (i.e., systematically 'zeroed'). This procedure would artificially inflate the mean silent synapse estimate (see Supplemental Information for more details).…”
Section: A Nonsilent Synaptic Populations and Fra Estimator Performancementioning
confidence: 99%